Incidence of metachronous contralateral breast cancer in Denmark 1978–2009. (16th October 2014) - Rasmussen, Christina Bording; Kjær, Susanne K; Ejlertsen, Bent; Andersson, Michael; Jensen, Maj-Britt; Christensen, Jane; Langballe, Rikke; Mellemkjær, Lene
Abstract: Background: Incidence of contralateral breast cancer (CBC) is much less studied than primary breast cancer. We aimed to assess incidence rates of CBC in relation to age, calendar period and time since first breast cancer. Methods: Using the nationwide Danish Cancer Registry, we identified 85 863 women with a first primary invasive breast cancer without distant metastases in Denmark during 1978–2009. Among these, 3120 women developed metachronous CBC. Crude incidence rates for CBC were calculated by age and calendar period at first breast cancer as well as time since first breast cancer. Mutual adjustments were made by use of Poisson regression models. Results: The incidence of CBC decreased with increasing age at first breast cancer. Before 1998, incidence rates of CBC showed little variation. The rates decreased by period of first primary from 546 per 10 5 person-years in 1993–97 to 328 per 10 5 person-years in 2003–09. After adjustment for age and calendar period, no clear trend was observed in the overall incidence according to time since first breast cancer. Conclusions: Occurrence of cancer in the contralateral breast seems to be rather independent of time passed since the first primary. The finding of a decreasing incidence of CBC after 1997 is likely to be due to more women receiving systemic adjuvant therapy such as tamoxifen and longer duration of this treatment as well as the introduction of aromatase inhibitors.